Kualitas Layanan Rawat Gabung dengan Tingkat Kepuasan Keluarga di Kamar Bayi Sehat - Ani Kurniasari; Irawan Danismaya; Egi Mulyadi; Azhar Zulkarnain Alamsyah (Journal of Telenursing (JOTING), 2026)
This study aims to analyze the relationship between the quality of outpatient care services and family satisfaction levels, providing a basis for hospitals to improve service quality. The research method used was a quantitative cross-sectional approach. Purposive sampling was used with 60 respondents. The results showed a p-value of 0.010, meaning p<0.050. The majority of respondents (93.3%) rated the quality of outpatient care services as high quality, and the majority (93.3%) were satisfied with the outpatient care they received. In conclusion, there is a relationship between the quality of outpatient care services and family satisfaction levels at the Healthy Baby Room.   Keywords: Family Satisfaction, Service Quality, Outpatient Care